Multiclass Compatible Sample Preparation for UHPLC–MS/MS Determination of Aflatoxin M1 in Raw Milk - Michlig, Nicolás; Repetti, María Rosa; Chiericatti, Carolina; García, Silvia R.; Gaggiotti, Monica Del Carmen; Basílico, Juan Carlos; Beldoménico, Horacio Ramón (Springer, 2018)
A sample preparation method for aflatoxin M1 (AFM1) determination in raw milk was optimized following the quick, easy, cheap, effective, rugged and safe (QuEChERS) strategy, as an alternative to the classic immunoaffinity column clean-up (IAC). The method was adapted to address the complexity of the milk matrix, and to be suitable for final determination by ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC–MS/MS). This approach proved also to be compatible with the simultaneous extraction of pesticide residues and other contaminants (mycotoxins). Regarding AFM1, satisfactory linearity was achieved and appropriate sensitivity was maintained, using matrix-matched calibration to compensate for the heavy ion suppression. The accuracy and precision, which were determined through recovery studies, were 70–95 %, with the relative standard deviation below 15 % in all of the cases. The limit of detection (LOD, 0.002 μg L−1) and limit of quantification (0.007 μg L−1) are compatible with current worldwide regulations (maximum levels of 0.5 and 0.05 μg L−1). The procedure was applied to samples that were naturally contaminated with a range of AFM1 at LOQ–0.187 μg L−1, with comparable results to IAC clean-up, which was employed as a reference method. Therefore, AFM1 determination in raw milk by UHPLC–MS/MS detection through the present QuEChERS extraction constitutes a reliable alternative to IAC clean-up and exhibits advantages related to cost, accessibility of materials and simplicity of operation.